Multi-scale ceramic TiC solves the strength-plasticity equilibrium problem of high entropy alloy - Hao Qi; Siruo Zhang; Chenghao Liu; Rongde Li; Shulin Dong; Guanglong Li; Yingdong Qu (Materials & Design)
High entropy alloys (HEAs) with single FCC structure exhibits unique structure and properties. However, lack of strength hinds the engineering application ability seriously. Therefore, it is urgent to propose effective methods and theories to enhance the strength while maintaining favorable plasticity. Introducing reinforced phases is one crucial research approach for improving the mechanical properties of HEAs. However, the resulting reduction in ductility has been neglected. In this work, we propose a novel multi-scale TiC coupling reinforced alloy which preserves the high plasticity while increasing the strength. The results demonstrate that TiC (μm) hinders the dislocations movement and improves strength through the second phase strengthening mechanism. Apart from acting as barriers to dislocation motion, the TiC (nm) also provides more dislocation sources in the distortion area at the junction with the matrix, which increasing the number of movable dislocations and enhancing the plastic strain capacity. Compared with the Al0.4 alloy, the tensile yield strength of the Al0.4-TiC (μm + nm) alloy is increased by 145 %, the ultimate tensile strength is up to 574 MPa, while maintaining a high plastic strain by 30.1 %. The addition of multi-scale ceramic phase TiC provides a novel approach to obtain high strength and high plasticity HEAs.